دور وأهمية الخدمات الارشادية الزراعية في تمكين وتعزيز دور المرأة الريفية في ليبيا - الهوشد مصباح سالم صالح (Aljameai)
ABSTRACT: This research study aimed to: 1) Identify the Levels of Empowering Libyan Rural Women (LELRW) through the extension educational services delivered by Rural Development Centers (RDCs) within Income–Generating Small Projects (IGSPs). LELRW was measured by using 3 indicators: a) Frequency of services delivery, b) degree of women’s benefits of these services, and c) women’s satisfaction about these services; and 2) Identify the relationships between the LELRW, the three indicators and the independent variables. A random sample of 203 rural women, graduates of RDCs, was personally interviewed by using a questionnaire designed and pretested for data collection. Frequencies, percentages, average means and simple Pearson’s correlation coefficients were used for data presentation and analysis. Results revealed that the LELRW of more than one half of the respondents (about 56%), was medium, high and very high. Statistically significant and positive correlation coefficients were found between the LELRW and: frequency of services delivery, degree of women’s benefits of these services, and women’s satisfaction about these services. Additionally, statistically significant and positive correlation coefficients were found between: a) Women’s benefits of services, and their participation in implementing the IGSPs, b) Women’s satisfaction about services and Women’s use of ICTs, Women’s contacts with extension personnel, and their participation in implementing the IGSPs.